Disruption of social play influences development of caution in juvenile ground squirrels - Ryan, William J.; Kuan, Marcello B.; Nunes, Scott (Frontiers in Ethology, 2024)
Play behavior is common in a range of mammalian species and can have important influences on early development. We evaluated possible influences of social play on the development of behavior along the caution/boldness continuum in juvenile Belding's ground squirrels (Urocitellus beldingi). We disrupted juvenile squirrels engaged in play by walking toward them until their play interactions stopped. We used undisrupted juveniles and juveniles disrupted while not engaged in play as controls. Caution was measured with behavioral tests during which a human intruder walked toward a squirrel and recorded the distances at which the squirrel first noticed and then fled from the intruder. Rates of social play were lower and play bouts were shorter in play-disrupted juveniles than in undisrupted and nonplay-disrupted juveniles. The distances at which juveniles noticed and fled from an intruder increased across the developmental period in which play primarily occurs, suggesting increases in caution across this interval. Increases in the distances to notice and flee from an intruder did not differ between undisrupted and nonplay-disrupted juveniles, but were greater in these groups than in playdisrupted juveniles. These results are consistent with social play behavior contributing to the development of cautious responses in juvenile U. beldingi.